ADENOID VEGETATIONS: EFFECTIVENESS OF THERAPY (REVIEW) - Mardonov Kh.; Djuraev J.A. (International Scientific and Current Research Conferences, 2024)
There are two points of view regarding the pharyngeal tonsil in cases of its increase in size. The first point of view is shared by a number of otorhinolaryngologists, who advocate the need to remove the enlarged pharyngeal tonsil even if it at least to some extent interferes with nasal breathing. The justification in this case is the circumstances that the developed volumetric enlargement of this tonsil negatively affects the child’s body, making it difficult to breathe through the nose, reducing the oxygen supply to the body, and disrupting metabolic processes. This leads to developmental delays in the child, including mental development [2]. At the same time, the functions of the nasal mucosa in cleansing, warming and humidifying the inhaled air suffer.